Repositioning Indonesia in the Changing Maritime Landscape of the Indo-Pacific Region - Pertiwi, Sukmawani Bela (UI Scholars Hub, 2020)
Indo-Pacific has been among the most contested regions in the past decade. After China demonstrated its ambitious goal in reviving maritime silk road with its military and economic presence, United States, India, Japan, and Australia formed a new coalition to counter this strategy. This paper aims to examine the position of Indonesia as a traditional regional maritime power in the context of this changing maritime landscape of the Indo-Pacific region. In doing so, this paper develops the concept of “the three faces of maritime power” which distinguishes maritime power into hard, soft, and normative maritime power. The findings of this paper indicates that Indonesia demonstrates less of its hard and soft power, but it capitalizes on its normative power to demonstrate its presence in the new maritime landscape of the Indo Pacific